The Black Bull : from Normandy to the Baltic with the 11th Armoured Division - Delaforce, Patrick (Stackpole military history series, 2011)
The sharp end -- In the beginning -- Weaponry -- Forming up -- "War is mostly about waiting" -- "Cry havoc" and "Let slip the dogs of war" -- Operation Epsom -- Interlude -- Operation Goodwood -- Another interlude -- Operation Bluecoat -- Breakout -- The great swan -- The taking of Antwerp -- Prelude and right flank to Market Garden -- Holland and the peel country -- In the bleak midwinter: October -- In the bleak midwinter: November -- In the bleak midwinter: leave -- In the bleak midwinter: December -- The Ardennes -- In the bleak midwinter: January -- In the bleak midwinter: February -- Operation Blockbuster: the Hochwald battle -- Another interlude: March -- The Rhine crossing and advance -- The battle for Teutoburger wald -- The River Weser crossing -- From the Weser to the Aller -- Towards the Elbe -- Belsen -- The last stretch -- Round-up